Lignin valorisation: Life Cycle Assessment (LCA) considerations for enabling Circular Bioeconomy - Kylili, Angeliki; Koutinas, Michalis; Georgali, Phoebe Zoe; Fokaides, Paris A. (My University, 2023)
Lignin constitutes the sole renewable aromatic resource found in abundance on Earth and does not call into question the ethics of diverting land from food to energy production. In view of that, the potential of lignocellulosic biomass in promoting the Circular Economy and Bioeconomy concepts in future biorefinery operations is widely acknowledged. Biorefineries can convert lignocellulosic biomass into high-value products, lessen their environmental effect, and hasten the advent of a sustainable and renewable future by incorporating cutting-edge technologies and doing thorough Life Cycle Assessment analysis. However, converting lignin into added-value products is a challenging field from technological, environmental, and economic perspectives. This work set out to determine the most critical environmental aspects expected to provide reliable evidence in support of lignin valorisation routes that enable the production of value-added products and bioenergy. Findings provide the necessary knowledge for decision-making in biorefineries aligned with the Circular Bioeconomy concept, like how decision-making relating to future biorefineries is facilitated. Highlights Environmental burdens of lignin-derived products valorisation due to complex lignin structure A limited number of LCA studies on the valorisation of lignin to added-value products Future lignin-based biorefineries development should be assessed using holistic, sustainable approaches LCA methodologies on environmental performance of promising lignin valorisation routes Controversial aspects of lignin valorisation under the Circular Bioeconomy concept Raised concerns as a result of the lignin fraction expected high demand Identified controversial environmental aspects linking lignin valorisation to adverse impacts.
Keywords: biorefinery; Circular Bioeconomy; environmental assessment; LCA; lignin; Lignocellulosic biomass; valorisation